2019
DOI: 10.3390/agronomy9050265
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids Regulate Antioxidant System and Protect Chloroplast Ultrastructure of Autotoxicity-Stressed Cucumber (Cucumis sativus L.) Seedlings

Abstract: Autotoxicity is a common problem being faced in protected vegetable cultivation system. Phytoremediation of plant autotoxicity is an emerging concept to minimize deterioration of soil environment and reduction of yield and quality of vegetable crops. Brassinosteroids (BRs) have been reported as a potential phytohormone to assist phytoremediation. However, the effects of BRs-induced autotoxicity stress on plant growth, photosynthesis and antioxidant defense system are poorly understood. Hence, we focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…When plants faces environmental stresses CAT, SOD, APX and GR protect plants from oxidative damage [38]. Similar reports were also published in bottle gourd and cucumber [39, 40]. In the present experiment, transcript level of CAT enhanced after 7, 14 and 21 DWD.…”
Section: Discussionsupporting
confidence: 89%
“…When plants faces environmental stresses CAT, SOD, APX and GR protect plants from oxidative damage [38]. Similar reports were also published in bottle gourd and cucumber [39, 40]. In the present experiment, transcript level of CAT enhanced after 7, 14 and 21 DWD.…”
Section: Discussionsupporting
confidence: 89%
“…Recent work has shown that EBR can increase epicuticular wax deposition (Santos da Fonseca et al, 2020). Improved maintenance of membrane functionality and overall cell compartmentation would also prevent water loss (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this chemical stress in recycled hydroponics, finding a suitable allelochemical detoxifying method (mainly phenolic compounds) either in the nutrient solution or improving the impaired physiological processes would sustain crop production, including strawberry. Research findings also suggested that the growth inhibitory effect of autotoxicity on cucumber was reduced by the application of epibrassinolide, which enhanced the photosynthetic capacity of leaves, maintained chloroplast integrity and thylakoid structures, and effectively alleviated the membrane damage caused by lipid peroxidation and root damage (Yang et al, 2019).…”
Section: Autotoxicity Mitigation Methods Used For Strawberrymentioning
confidence: 95%